Violence against Women and Sexual and Reproductive Rights - Bermúdez Valdivia, Violeta (2008)
This paper is about the violence against the women and over its sexual and reproductive rights, from a human rights approach. The author remarks the constitutionalizing of the human rights and she says that addressing the violence against the women from this approach is valuable. That allows us to generate regulatory provisions that explicitly reflects the women’s rights.  Likewise, it should be said that violence against the women is a human rights problem, in this way, the State and society have obligations to obey to their nationals and to the international community. These obligations came from the diverse international instruments in which the violence against women is considered, as well as the obligations that derivate from these instruments in order to eradicate it. Also, it is understood that the sexual and reproductive rights had been developed in an international level, that is why States are expected to take measures to their protection. Later, it been analyzed in three situations the relationship between the violence against the women and the affectation of the sexual and reproductive rights: i) the sexual violence against the women during marriage; ii) compulsive practices of reproductive control; iii) the sexual violation as a crime against the humanity. It is important have a human rights approximation to these intersections because they are useful at the time to plan public policies. Likewise, it is said that is necessary have a gender approach to have a wide view of this situation. In this way, we will have the correct answers to the prevention, attention and eradication of this problem. For it, also, is necessary that the conceptual development in the international law set in the national law. It should be stressed that the violence against women does not acquires a one way only, but it revealed in many ways, all of them hurts their integrity and dignity. Finally, it is indicated that it should be made visible the impact of the violence against women in order to take consciousness about the magnitude of this problem. It will serve us as a reference to implement public policies that follows eradicate this problem.